Investigation Of Character Values In Students Through Festivals In Minangkabau Culture Subjects - Berlian Permata Mudalensia; Liza Liza; Meldawati Meldawati (PT. Anagata Sembagi Education, 2024)
This research aims to describe the instillation of character values in students through cultural festivals using a descriptive quantitative approach. Data collection was conducted through surveys, which assessed students' understanding of the character values imparted during various festival activities, such as *baralek gadang*, *randai*, traditional dance, *manampih bareh*, and *petatah petitih*. The results reveal that the majority of students possess a good to very good understanding of these character values, as demonstrated by the data analysis, which showed a score of 87.54%. The research findings suggest that the Minangkabau cultural festival plays a significant role in shaping students' positive attitudes and character development by promoting important values like cooperation, tolerance, responsibility, and cultural pride. These results underscore the effectiveness of using local cultural practices as a means of character education. The integration of local wisdom, such as the Minangkabau festival, can enhance students' personal growth and moral development, making it a vital component in higher education curricula. The study highlights the broader benefits of embedding cultural traditions within the educational system to foster a stronger connection between students and their cultural heritage, while simultaneously building essential character traits